2011
DOI: 10.1177/1753425911423270
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine release by neutrophils in chronic obstructive pulmonary disease

Abstract: Neutrophils are among the first cells to arrive at the site of injury. Chemokines secreted by neutrophils affect the migration of both neutrophils and other inflammatory cells, such as monocytes. It has been reported that LPS-induced release of IL-8 (CXCL-8) by neutrophils is amplified by neutrophil-derived TNF-α. We hypothesize that chemokine release by neutrophils is altered in chronic obstructive pulmonary disease (COPD) compared with healthy controls and that TNF-α may be involved in this alteration. Perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…MIP-1β contributes substantially to the development of lung inflammation following exposure to tobacco smoke [26] . The levels of IL-6, IL-8, TNF-α, IP-10, MCP-1, MIP-1α and MIP-1β were increased in the sputum and/or serum of patients with stable COPD or during exacerbation compared with controls [23][24][25] . Therefore, these cytokines are cardinal markers of airway inflammation in COPD patients.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…MIP-1β contributes substantially to the development of lung inflammation following exposure to tobacco smoke [26] . The levels of IL-6, IL-8, TNF-α, IP-10, MCP-1, MIP-1α and MIP-1β were increased in the sputum and/or serum of patients with stable COPD or during exacerbation compared with controls [23][24][25] . Therefore, these cytokines are cardinal markers of airway inflammation in COPD patients.…”
Section: Resultsmentioning
confidence: 88%
“…IL-6 contributes to the pathogenesis of the autoimmune response observed in the lungs of the patients with more severe COPD; IL-8 plays a major role in neutrophil chemotaxis caused by alveolar macrophage-derived conditioned media of COPD; TNF-α is an important chemotactic protein for neutrophils [22] ; IP-10 is a chemokine strongly associated with viral infection of COPD [23] ; MCP-1 is involved in the migration of macrophages into the small airways, thus contributing to the inflammatory load associated with COPD [24] ; neutrophilderived MCP-1, MIP-1α, and MIP-1β are involved in macrophage recruitment into inflamed tissue during COPD [25] . MIP-1β contributes substantially to the development of lung inflammation following exposure to tobacco smoke [26] .…”
Section: Resultsmentioning
confidence: 99%
“…We also found that carbocisteine reduced the production of IL-6 and IL-8, decreased the expression of inflammatory cytokines such as IL-6 and TNF-α, reduced the chemokines such as IL-8, IP-10 and MIP-1β (important factors related to the pathogenesis of COPD [20][21][22][23][24]), and exhibited exceptional anti-inflammatory ability. These findings extended our study on the cytoprotective role of carbocisteine from H 2 O 2 , namely, the inhibitory effects of carbocisteine on the induction of pro-inflammatory cytokines and chemokines by H 2 O 2 .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, components have been identified that increase the longevity of neutrophils in COPD, which substantially adds to the accumulation of these cells in the lungs. Finally, in comparison with those of healthy individuals, the neutrophils of COPD seem to respond differently to many chemical signals that normally regulate the immune response [69][70][71]. This has impeded the progress of research to the causes and especially to possible interventions for COPD.…”
Section: Reviewmentioning
confidence: 90%
“…Because of these findings, it has been suggested that TNF-a levels are the reason why the progression of COPD slows down if people quit smoking [78]. However, a later study using an TNF-a antagonist suggests the role of TNF-a is altered in COPD [71].…”
Section: Lung Infiltrationmentioning
confidence: 97%